2015
DOI: 10.1021/cs501709d
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Chemically Essential Interactions Based on Active Site Alignments and Quantum Chemical Calculations: A Case Study on Glycoside Hydrolases

Abstract: We here use an approach of active site alignment and clustering of many evolutionarily distant enzymes catalyzing alike reactions to identify conserved residues/interactions that may play key chemical roles in catalysis. Then density functional theory (DFT) calculations on cluster models are used to investigate the chemical essentialness of such residues/interactions and its mechanistic basis. We apply this approach to 130 glycoside hydrolases (GHs) of the (βα) 8 -barrel fold. These enzymes adopt either a clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 82 publications
(166 reference statements)
0
11
0
Order By: Relevance
“…GH18 chitinases are an intriguing case because all theoretical and experimental work to date describe the intermediate as protonated (i.e., oxazolinium ion) ,,. This is particularly surprising because the assisting and the acid/base residues (Asp142 and Glu144, respectively, in Serratia mascescens ( Sm) ChiB) are linked by a hydrogen bond and thus they share a proton (Figure c) . This increases the p K a of the assisting residue with respect to the situation when both residues are not linked (Figure b) or they are in solution .…”
Section: Introductionmentioning
confidence: 99%
“…GH18 chitinases are an intriguing case because all theoretical and experimental work to date describe the intermediate as protonated (i.e., oxazolinium ion) ,,. This is particularly surprising because the assisting and the acid/base residues (Asp142 and Glu144, respectively, in Serratia mascescens ( Sm) ChiB) are linked by a hydrogen bond and thus they share a proton (Figure c) . This increases the p K a of the assisting residue with respect to the situation when both residues are not linked (Figure b) or they are in solution .…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the existence of several studies on the mechanisms of glycosidases, there are some central questions that remain to be clarified, such as the charge distribution between the anomeric carbon and the ring oxygen at transition state . Additionally, many of the glycosidases have uncommon catalytic mechanisms, such as substrate assisted autocatalysis or have uncommon sugar substitutions (i.e., phosphorylation) that affect the mechanism …”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen bond stability analysis showed that the nucleophile GLN207 maintained the hydrogen bond throughout the entire 20-ns simulation ( Supplementary Figure S3 ). This nucleophilic residue is responsible for enzyme-substrate interaction [ 55 , 56 ]. Another active site residue, THR210, formed a hydrogen bond in the hydrophobic state.…”
Section: Resultsmentioning
confidence: 99%